Staying in the game: a pilot study examining the efficacy of protective headgear in an animal model of mild traumatic brain injury (mTBI). (19th September 2017) - Candy, Sydney; Ma, Irene; McMahon, Jill M; Farrell, Michael; Mychasiuk, Richelle
ABSTRACT: Primary Objective: Rugby is one of the few contact sports that do not mandate protective headgear, possibly because studies have shown poor efficacy for protection related to concussion pathology with existing headguards. Research Design : Following innovative material technology utilization to produce headgear believed to have protective capabilities, this study examined the effects of a soft-shell headgear constructed from a novel viscoelastic material, on both behaviour and serum biomarkers after high and average impact force mild traumatic brain injuries (mTBI). Methods and Procedures : Seventy-five male Sprague Dawley rats were divided into five groups: control, average - 37G impact, with and without headgear, and high - 106G impact, with and without headgear. Rats were sacrificed at 3 or 48 hours and serum samples were analyzed for levels of TNF-α, NEF-L, and GFAP . Animals sacrificed at 48 hours also underwent testing for balance and motor coordination, and exploratory/locomotor behaviour. Main Outcomes and Results : The novel headgear offered significant protection against mTBI symptomology and biomarkers in the group that experienced an average impact force, but only moderated protection for the animals in the high impact group. Conclusions : This innovative headgear may prevent some of the negative sequel associated with concussion pathology.